Pregnane X receptor is required for interleukin-6 mediated down-regulation of cytochrome P450 3A4 in human hepatocytes - Yang, Jian (2010)
Cytochrome P450 3A4 (CYP 3A4) is the most abundant cytochrome P450 enzyme in human liver and metabolizes more than 60% of prescribed drugs in human body. Patients with liver conditions such as cirrhosis show increased secretion of cytokines (e.g, interleukin-6) and decreased capacity of oxidation of many drugs. In this study, we provided molecular evidence that cytokine secretion directly contributed to the decreased capacity of oxidative biotransformation in human liver. After human hepatocytes were treated with IL-6, the expression of CYP3A4 decreased at both mRNA and protein levels, so did the CYP3A4 enzymatic activity. Meanwhile, the repression of CYP3A4 by IL-6 occurred after the decrease of pregnane X receptor (PXR) in human hepatocytes. The PXR-overexpressed cells (transfected with human PXR) increased the CYP3A4 mRNA level, and the repression of CYP3A4 by IL-6 was greater in the PXR-overexpressed cells than in the control cells. Further, PXR-knockdown (transfected with siPXR construct) decreased the CYP3A4 mRNA level with less repression by IL-6 than in the control cells transfected with corresponding vector. Collectively, our study suggests that PXR is necessary for IL-6-mediated repression of the CYP3A4 expression in human hepatocytes.